2020
DOI: 10.3389/fcimb.2020.596750
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Gut Microbiota of Adult Mosquitoes From Eight Locations in Hainan, China

Abstract: The midgut microbial community composition, structure, and function of field-collected mosquitoes may provide a way to exploit microbial function for mosquito-borne disease control. However, it is unclear how adult mosquitoes acquire their microbiome, how the microbiome affects life history traits and how the microbiome influences community structure. We analyzed the composition of 501 midgut bacterial communities from field-collected adult female mosquitoes, including Aedes albopictus, Aedes galloisi, Culex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Firmicutes are abundant in the digestive tracts of Spodoptera litura, Manduca sexta, Helicoverpa armigera, and several other lepidopterans [17]. Absolute dominance in the abundance of Proteobacteria in G. molesta [18], Bombyx mori [23,54], N. lugens [25,51,55], mosquitoes [42,56], and Triatoma sordida [57] has been confirmed. The high abundance of Firmicutes on wild oats is due to better absorption of different nutrients.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Firmicutes are abundant in the digestive tracts of Spodoptera litura, Manduca sexta, Helicoverpa armigera, and several other lepidopterans [17]. Absolute dominance in the abundance of Proteobacteria in G. molesta [18], Bombyx mori [23,54], N. lugens [25,51,55], mosquitoes [42,56], and Triatoma sordida [57] has been confirmed. The high abundance of Firmicutes on wild oats is due to better absorption of different nutrients.…”
Section: Discussionmentioning
confidence: 83%
“…In recent years, more insect microbial communities have been discovered and studied. Studies have been reported in honeybees [34][35][36][37], fruit flies [38][39][40], mosquitoes [41,42], Dectes texanus [43], and termites [44,45], as well as in lepidopteran pests, such as Grapholita molesta [18,[46][47][48], Carposina sasakii [46,47], and Cydia pomonella [47]. The gut microbial community of the honeybee has stable species and structure, and there are many unique microbial types in different regions of Apis mellifera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…atroparvus , the vast majority from the phylum Proteobacteria . Most of the bacterial taxa herein reported have been described as part of the microbiota in culicid mosquitoes ( Dada et al, 2014 ; Muturi et al, 2016 ; Rocha-David et al, 2016 ; Hegde et al, 2018 ; Kang et al, 2020 ) including Anopheles from different geographic regions ( Rani et al, 2009 ; Djadid et al, 2011 ; Wang et al, 2011 ; Boissiere et al, 2012 ; Gimonneau et al, 2014 ; Ngo et al, 2015 ; Bogale et al, 2020 ; Galeano-Castañeda et al, 2020 ; Zoure et al, 2020 ; Feng et al, 2021 ; Silva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The alpha diversity (i.e., Shannon diversity, Chao1 richness and coverage) was determined using the “vegan” package in R (version 3.6.2) [ 27 ]. Soil basic indexes (ECe, pH, clay, silt, sand, K + , Na + , Ca 2+ , Mg 2+ , SOC, AN, AP, AK, ALP, invertase, urease and CAT) were evaluated using one-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%